The big Data Phenomenon – the Business and Public Impact - Chroneos Krasavac, Biljana; Soldic Aleksic, Jasna; Petkovic, Goran (Industrija, 2016)
The subject of the research in this paper is the emergence of big data phenomenon and application of big data technologies for business` needs with the specific emphasis on marketing and trade. The purpose of the research is to make a comprehensive overview of different discussions about the characteristics, application possibilities, achievements, constraints and the future of big data development. Based on the relevant literature, the concept of big data is presented and the potential of large impact of big data on business activities is discussed. One of the key findings indicates that the most prominent change that big data brings to the business arena is the appearance of new business models, as well as revisions of the existing ones. Substantial part of the paper is devoted to the marketing and marketing research which are under the strong impact of big data. The most exciting outcomes of the research in this domain concerns the new abilities in profiling the customers. In addition to the vast amount of structured data which are used in marketing for a long period, big data initiatives suggest the inclusion of semi-structured and unstructured data, opening up the room for substantial improvements in customer profile analysis. Considering the usage of information communication technologies (ICT) as a prerequisite for big data project success, the concept of Networked Readiness Index (NRI) is presented and the position of Serbia and regional countries in NRI framework is analyzed. The main outcome of the analysis points out that Serbia, with its NRI score took the lowest position in the region, excluding Albania. Also, Serbia is lagging behind the appropriate EU mean values regarding all observed composite indicators - pillars. Further on, this analysis reveals the domains of ICT usage in Serbia, which could be focused for an improvement and where incentives can be made. These domains are: political and regulatory environment, business and innovation environment, business usage, government usage and social impacts of ICT.
Keywords: Technology; Organization